Global Health as "umbrella term" - a qualitative study among Global Health teachers in German medical education - Matthias Havemann; Stefan Bösner (BMC, 2018)
Abstract Background The increasing impact of globalisation on healthcare demands new knowledge, skills and attitudes from healthcare professionals. One consequence of this is the rise of Global Health (GH) programs in health education all over the world. In Germany no consensus exists on what GH is and how it should be taught. This study used a grounded theory approach. We conducted eleven in-depth interviews with GH teachers in German medical education to ask them about their views on Global Health and the approaches they took in teaching these topics. Data collection and Analysis informed each other and followed an inductive approach. Results Our research identified three major questions: (1) What is GH? (2) What belongs to GH? (3) How can GH be taught? A central finding of our study is the understanding of GH as an umbrella term. We show how this understanding helps clarify the relation between GH and Public Health, International Health and Tropical medicine. At the core of GH we see the supraterritorial determinants of health. Surrounding the core, we describe a wide variety of topics that are a facultative, but not necessarily a compulsory part GH. One of the key characteristics of GH within all its aspects is its multidisciplinary nature. Based on this understanding we present models about the content of GH, how it can be taught and how GH teaching improves and strengthens overall medical education. Conclusions This is to our knowledge the first study that conducts in-depth interviews with GH teachers to explore the practical understanding of GH in medical education. While the generalisability of our results needs to be subject of further research, the models presented can help shape the future discourse around GH and its integration into medical education.